Adjusting accommodation microenvironment for Cu+ to enhance oxidation inhibition for thiophene capture - Li, Yu‐Xia; Jin, Meng‐Meng; Shi, Shu; Qi, Shi‐Chao; Liu, Xiao‐Qin; Sun, Lin‐Bing (AIChE journal, 2021)
Cu+‐containing materials have great potentials in various applications like adsorptive desulfurization. Nevertheless, their applications are severely obstructed by poor stability of Cu+ in air. Here, we first clarify the mechanism of Cu+ oxidation by first‐principle calculations and demonstrate that moisture accelerates Cu+ oxidation dramatically. Then, the microenvironment of Cu2O‐modified HKUST‐1, a typical metal‐organic framework, is adjusted from hydrophilic to hydrophobic with polydimethylsiloxane coating (producing Cu2O@HK@P). This isolates moisture from pores and enhances the stability of Cu+ significantly even under oxygen atmosphere. Cu+ in Cu2O@HK@P preserves well after exposed to air for 6 months, while Cu2O@HK lose almost all Cu+ for 2 weeks. The optimal Cu2O@HK@P can remove 540 μmol g−1 of thiophene from hydrous fuel, which is much superior to Cu2O@HK (227 μmol g−1) and most reported adsorbents. Our strategy can also be applied to stabilize Cu+ in various materials including zeolite, mesoporous silica, and activated carbon.